Genetic Analysis of 'PAX6-Negative' Individuals with Aniridia or Gillespie Syndrome. - Morad Ansari; Jacqueline Rainger; Isabel M Hanson; Kathleen A Williamson; Freddie Sharkey; Louise Harewood; Angela Sandilands; Jill Clayton-Smith; Helene Dollfus; Pierre Bitoun; Francoise Meire; Judy Fantes; et al. (PLoS ONE)
We report molecular genetic analysis of 42 affected individuals referred with a diagnosis of aniridia who previously screened as negative for intragenic PAX6 mutations. Of these 42, the diagnoses were 31 individuals with aniridia and 11 individuals referred with a diagnosis of Gillespie syndrome (iris hypoplasia, ataxia and mild to moderate developmental delay). Array-based comparative genomic hybridization identified six whole gene deletions: four encompassing PAX6 and two encompassing FOXC1. Six deletions with plausible cis-regulatory effects were identified: five that were 3' (telomeric) to PAX6 and one within a gene desert 5' (telomeric) to PITX2. Sequence analysis of the FOXC1 and PITX2 coding regions identified two plausibly pathogenic de novo FOXC1 missense mutations (p.Pro79Thr and p.Leu101Pro). No intragenic mutations were detected in PITX2. FISH mapping in an individual with Gillespie-like syndrome with an apparently balanced X;11 reciprocal translocation revealed disruption of a gene at each breakpoint: ARHGAP6 on the X chromosome and PHF21A on chromosome 11. In the other individuals with Gillespie syndrome no mutations were identified in either of these genes, or in HCCS which lies close to the Xp breakpoint. Disruption of PHF21A has previously been implicated in the causation of intellectual disability (but not aniridia). Plausibly causative mutations were identified in 15 out of 42 individuals (12/32 aniridia; 3/11 Gillespie syndrome). Fourteen of these mutations presented in the known aniridia genes; PAX6, FOXC1 and PITX2. The large number of individuals in the cohort with no mutation identified suggests greater locus heterogeneity may exist in both isolated and syndromic aniridia than was previously appreciated.